Perbedaan Prestasi Belajar Antara Siswa Obesitas Dan Tidak Obesitas Pada Siswa Sekolah Dasar Di Kota Kediri - Sumy Dwi Antono (coba, 2017)
Obesity is a pathological condition with the presence of excessive fat storage than is required for the function of the body. In general, in Indonesia the problem of obesity in children today do not get enough attention from the pediatrician, because they are more preoccupied by the problem of malnutrition. Children with obesity or overweight can lower the level of intelligence, because the activity and creativity of children into decline, and then with excess weight tend to be lazy. The purpose of this study was to determine students' learning achievement in obese and non-obese elementary school in Kediri. The design study is observational analytic with cross sectional design, with research subjects are students in grades 3 SDN SDN Bandar Lor 1,2,3 and 1,2,3 Bandar Kidul obese and non-obese Kediri many as 84 students. The data were analyzed Bivariat to compare student achievement are obese and non-obese by Using test of independent samples t test. The test results One Sample Kolmogorov-Smirnov Test results obtained P> 0.05, the value of P = 0.795 for respondent data are not obese and P = 0.511 for the respondent data obesity. The conclusion is that the data respondents are not obese, and obesity is a normal distribution of data. Based on the results of statistical tests Independent Samples T Test data showed that P value = 0.00> 0.005, so the conclusion is There were significant differences between students' learning achievement obese and non-obese, namely: learning on student achievement obesity was lower (mean = 68, 32) compared to students who are not obese (mean = 77.41) Keywords: learning achievement, obesity